ANALISIS SOSIAL-EKONOMI SAMPAH PLASTIK DI PERAIRAN PESISIR TERHADAP PRODUKTIVITAS DAN KESEJAHTERAAN NELAYAN: STUDI KASUS DESA MORODEMAK, DEMAK - Yeremia Petra Sigalingging; Tegar Hermawan; Penesta Tia Tira Sinulingga; Talenta Vena Insan; Muhammad Ghozi Alghifari; Ahmad Fakhri Agusvian; Muhammad Dafa Umar Reza; Dinda Ayu Andhini; Try Satria Ismanto; Indah Susilowati (Universitas Nias Raya, 2026)
This study aims to analyze the relationship of plastic waste accumulation in coastal waters on the productivity and welfare of fishermen in Morodemak Village, Demak Regency. Plastic waste is one of the most common forms of marine pollution found in coastal and marine areas of Indonesia, including in fishing areas, which can degrade the quality of marine ecosystems and disrupt local fishermen's fishing activities. The accumulation of plastic waste impacts fishing gear disruption, increases operational costs, and decreases catch yields, thus negatively impacting fishermen's productivity and income. This study uses a quantitative approach with surveys and interviews with fishermen in Morodemak Village, as well as statistical data analysis to examine the relationship between the level of plastic waste accumulation and catch productivity and fishermen's economic welfare. The results are expected to provide an empirical picture of the impact of marine plastic pollution on the small-scale fisheries sector, as well as recommendations for waste management policies for the sustainability of coastal fishermen's livelihoods. This study contributes to the literature on the relationship between marine pollution and the fisheries economy, as found by previous studies that showed a negative relationship between marine debris and fisheries productivity in other regions.